(untitled) (The International Journal of Educational Sciences and Arts, 2024)
This study addresses the role of communication in crisis management in the field of public relations at Saudi Aramco, highlighting the importance of effective communication as a strategic tool in enhancing the ability of institutions to deal with crises. It aims to understand how communication affects institutional performance, especially in light of the difficult circumstances that institutions may face during crises. The study used a descriptive methodology to collect data, focusing on how to use different means of communication, including social media platforms, to enhance internal and external communication. The role of public relations in building trust with the public was also reviewed, which contributes to improving the institution’s reputation during crises. The results show that good planning for communication means is an essential element in crisis management, as it requires clearly defining responsibilities for each individual in the team, and providing the necessary information to all concerned parties. In addition, the study concluded that continuous training for the crisis management team is necessary to develop their skills in dealing with crises effectively. The study recommended the need to enhance the use of social media platforms as a tool for immediate communication with the public, which helps in enhancing and developing mechanisms for direct communication with the public in all its spectrums and the optimal continuation of improvement and development processes for the operations and services provided by the company, which contributes to maintaining the positive and distinctive mental image enjoyed by the company. In conclusion, the study emphasizes that effective communication is a vital element in crisis management, and institutions must invest in developing integrated communication strategies to ensure their rapid and effective response to challenges.